Effect of dietary patterns and nutritional supplementation in the management of endometriosis: a review - Zhou, Liyuan; Liu, Boya; Jian, Xian; Jiang, Lili; Liu, Kuiran (Frontiers in Nutrition, 2025)
Endometriosis is an estrogen-dependent chronic inflammatory disease which causes dysmenorrhea, chronic pelvic pain, and infertility in women of childbearing age, significantly impacting their quality of life and physical and mental health. The etiology of endometriosis remains unclear, with oxidative stress and inflammation currently thought to play pivotal roles in its pathophysiology. Epidemiological studies and clinical trials indicate that varying dietary patterns and specific nutrient supplementation can influence oxidative stress markers and levels of inflammatory factors and related pathways, potentially impacting the progression of endometriosis. In this review, we summarize the roles of oxidative stress and inflammation in endometriosis and thoroughly examine the current understanding of the effect of dietary patterns and nutrient supplementation in treating endometriosis. This study suggests that nutrients may prevent the occurrence of endometriosis by modulating levels of inflammatory factors, regulating angiogenesis, and influencing the metabolism of estrogen pathways. The findings might provide new insights into the treatment of endometriosis patients and the potential benefits of dietary patterns and nutrient supplementation in patients with endometriosis.